Five-Year Changes in Biologic Risk Factors and Risk of Type 2 Diabetes: Are Attained But Not Initial Risk Factor Levels of Importance? - Gast, G.-C. M.; Spijkerman, A. M. W.; van der A, D. L.; Jacobs-van der Bruggen, M. A. M.; Verschuren, W. M. M. (American journal of epidemiology, 2012)
Independent effects of changes in biologic risk factors on type 2 diabetes incidence remain unclear. The authors examined whether associations between changes in biologic risk factors and diabetes risk are driven by initial or attained risk factor levels. Biologic risk factors were measured at baseline and at each 5-year interval follow-up (rounds 2, 3, and 4) among 4,204 initially healthy men and women, aged 20-59 years, participating in the Dutch Doetinchem Cohort Study (1987-2007). Time-dependent Cox regression analyses were used to analyze associations between changes in waist circumference, blood pressure, and high density lipoprotein cholesterol (HDL cholesterol) and incident diabetes, adjusted for initial or attained levels; 130 diabetes cases occurred during 9 years of follow-up. Five-year increases in waist circumference and blood pressure and decreases in HDL cholesterol were positively associated with risk of diabetes after adjustment for initial levels but no longer after adjustment for attained levels: waist circumference (hazard ratio (HR) = 0.86, 95% confidence interval (CI): 0.69, 1.07), systolic blood pressure (HR = 0.96, 95% CI: 0.84, 1.10), diastolic blood pressure (HR = 0.96, 95% CI: 0.87, 1.06), and HDL cholesterol (HR = 0.91, 95% CI: 0.81, 1.01). In conclusion, the associations between changes in biologic risk factors and risk of diabetes are mainly driven by the attained levels. Hence, not the prior changes, but the attained levels seem to be of importance with regard to diabetes risk.